دراسة تأثير إضافة نشاء الذرة في بعض الخصائص الحسية والكيميائية للشعيرية سريعة التحضير (نودلز) المصنعة من دقيق الفول. (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
Cornstarch has been added, with percentages of ( 5%, 10%, 15%,20% and 25%), to flour beans both types paste (peeled and non-peeled) prepared for the manufacture of a quick vermicelli preparation (noodles), in order to study the effect of the addition of some chemical and organoleptic characteristics of this product and to determine the ideal proportion of corn starch added. The study has shown that there is an inverse relationship between the reduction of protein content and the increase of the fat percentage and the increase of starch proportion up to (25%) in both kinds of bean noodles: peeled and unpeeled.Increasing the ratio of starch above 15% has affected negatively the resulted noodles colour and some organoleptic characteristics such as taste and smell with the emergence of a gradual improvement of the appearance of noodles that resulted from flour peeled beans.Finally , it was found that the best ratio of added starch is 15%تم إضافة نشاء الذرة بنسب محددة (5%, 10%, 15%, 20%, 25%) إلى عجينة دقيق الفول بنوعيه (المقشور، وغير المقشور) المعدة لصناعة الشعيرية سريعة التحضير (النودلز), بهدف دراسة تأثير هذه الإضافة في بعض الخصائص الكيميائية والحسية لهذا المنتج, والوصول إلى تحديد النسبة المثالية من نشاء الذرة المضاف. لقد أظهرت الدراسة وجود علاقة عكسية بين انخفاض محتوى البروتين، وزيادة نسبة الدسم، وارتفاع نسبة النشاء حتى (25%) في نوعي نودلز الفول المقشور، وغير المقشور كليهما.إن زيادة كمية النشاء عن (15%), قد أثرت سلباً، وبشكل معنوي، في لون النودلز الناتجة, وكذلك أثرت سلباً، وبشكل معنوي، في بعض الخصائص الحسية كالطعم والرائحة, مع ظهور تحسن تدريجي لمظهر النودلز الناتجة عن دقيق الفول المقشور.أخيراً , تبين أن أفضل نسبة للنشاء المضاف هي15 %.